FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN PUBLIK NON KEUANGAN - SIENNY WIGUNA; DEWI SARI WIJOYO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to get empirical evidence influence the inside ownership, outside concentrated ownership, return on assets, firm’s size, current ratio, debt to equity ratio to dividend policy. This research focus on non financial companies listed in Indonesia Stock Exchange for the period of 2012 until 2014. The data collection used purposive sampling method by using 102 companies meet the criteria and take as sample. The statistical method used in this research is multiple regression to see the contribution of each variable influence dividend policy. The result of this study shows that inside ownership, firm’s size, current ratio, and debt to equity ratio do not affect dividend policy. In the other hand, outside concentrated ownership and return on assets significantly affect on dividend policy